1997
DOI: 10.1002/(sici)1099-0844(199712)15:4<237::aid-cbf746>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Non-functional role of syntaxin 2 in insulin exocytosis by pancreatic β cells

Abstract: This study was designed in order to examine the expression and functional role of syntaxin 2/epimorphin in pancreatic beta cells. Northern blot analysis revealed that syntaxin 2 mRNA was able to be detected in mouse beta TC3 cells, but not in isolated mouse islets. In agreement with this result, immunoblot analysis detected an appreciable amount of syntaxin 2 protein in beta TC3 cells, but not in mouse islets. Immunohistochemistry of the mouse pancreas demonstrated that syntaxin 2 was little evident in islet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Other reports include synaptotagmin III (59,60), rabphilin and rab3A (61), and cellubrevin (62). Evidence is available that syntaxin 1 but not syntaxin 2 is involved in ␤-cell exocytosis (63)(64)(65). VAMP-2 and cellubrevin are required for Ca 2ϩ -stimulated exocytosis but may not be involved in GTP-stimulated exocytosis (34).…”
Section: Exocytosis In the Pancreatic ␤-Cellmentioning
confidence: 99%
“…Other reports include synaptotagmin III (59,60), rabphilin and rab3A (61), and cellubrevin (62). Evidence is available that syntaxin 1 but not syntaxin 2 is involved in ␤-cell exocytosis (63)(64)(65). VAMP-2 and cellubrevin are required for Ca 2ϩ -stimulated exocytosis but may not be involved in GTP-stimulated exocytosis (34).…”
Section: Exocytosis In the Pancreatic ␤-Cellmentioning
confidence: 99%
“…The gene that encodes EPM also encodes syntaxin-2, a protein that has been shown to function during targeting/ fusion of intracellular vesicles with the plasma membrane (Bennett et al, 1993;Pelham, 1993). Although syntaxins have been shown to act at the cytoplasmic face of membranes (Brose, 1993;Pelham, 1993;Rothman, 1994;Wheeler et al, 1996;Jagadish et al, 1997), the subcellular localization of syntaxins can be modulated through various mechanisms (Hui et al, 1997;Jagadish et al, 1997;Rodger et al, 1998;Quiñones et al, 1999), and syntaxins have been found at the cell surface at least transiently (Hirai et al, 1993(Hirai et al, , 1998Smirnova et al, 1993a,b;Butt et al, 1996;Nagamatsu et al, 1997;Guo et al, 1998). Evidently, these complex and versatile proteins can perform multiple functions, and it will be a considerable challenge to discover how these diverse roles are related.…”
Section: Epm Is a Member Of The Syntaxin Familymentioning
confidence: 99%
“…Previous studies have shown that t-SNARE family proteins are expressed in islets of Langerhans and regulate insulin release (Jacobsson et al 1994;Wheeler et al 1996;Nagamatsu et al 1999). However, the expression of EPM/syntaxin 2 in islets was found to be low and the function was unrelated to the insulin exocytosis pathway (Nagamatsu et al 1997). Our data demonstrate that EPM protein is expressed in the micro blood vessels and mesenchymal cells inside islets, which therefore suggests that it may not play a role in insulin exocytosis, though it could play a role in islet morphogenesis (Lammert et al 2001;Konstantinova & Lammert 2004).…”
Section: Discussionmentioning
confidence: 96%
“…1999). However, the expression of EPM/syntaxin 2 in islets was found to be low and the function was unrelated to the insulin exocytosis pathway (Nagamatsu et al . 1997).…”
Section: Discussionmentioning
confidence: 99%